2022
DOI: 10.3389/fmicb.2022.893603
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Heavy Metals Biosorption via Artificial Neural Network: A Case Study of Cobalt (II) Sorption by Pseudomonas alcaliphila NEWG-2

Abstract: The definitive screening design (DSD) and artificial neural network (ANN) were conducted for modeling the biosorption of Co(II) by Pseudomonas alcaliphila NEWG-2. Factors such as peptone, incubation time, pH, glycerol, glucose, K2HPO4, and initial cobalt had a significant effect on the biosorption process. MgSO4 was the only insignificant factor. The DSD model was invalid and could not forecast the prediction of Co(II) removal, owing to the significant lack-of-fit (P < 0.0001). Decisively, the predictio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 63 publications
0
21
0
Order By: Relevance
“…Almost 40% of patients undergoing craniotomy develop infection at least once, such as pneumonia independent of mechanical ventilation (15%), ventilator-associated pneumonia (VAP; 23%), or urinary tract infection (UTI; 9%), and postoperative surgical site infections (SSIs) occur in 9% ( Kourbeti et al., 2015 ). Moreover, invasive procedures, including central venous catheter, urinary catheter, mechanical ventilation, and tracheostomy, are potential risk factors during the first 48 h in the ICU, predicting an ICU-acquired infection in our study due to the fact that these tubes provide an ideal opportunity for bacterial adhesion and biofilm formation ( Sottile et al., 1986 ; Elsayed et al., 2022 ). The rapid colonization of microbiota contributes to the infection.…”
Section: Discussionmentioning
confidence: 94%
“…Almost 40% of patients undergoing craniotomy develop infection at least once, such as pneumonia independent of mechanical ventilation (15%), ventilator-associated pneumonia (VAP; 23%), or urinary tract infection (UTI; 9%), and postoperative surgical site infections (SSIs) occur in 9% ( Kourbeti et al., 2015 ). Moreover, invasive procedures, including central venous catheter, urinary catheter, mechanical ventilation, and tracheostomy, are potential risk factors during the first 48 h in the ICU, predicting an ICU-acquired infection in our study due to the fact that these tubes provide an ideal opportunity for bacterial adhesion and biofilm formation ( Sottile et al., 1986 ; Elsayed et al., 2022 ). The rapid colonization of microbiota contributes to the infection.…”
Section: Discussionmentioning
confidence: 94%
“…67 At this threshold, a signicant coefficient indicates a less than 5% chance of wrongly concluding a link between a variable and the response when none exists. 66,68 Unfortunately, our model exhibits a signicant lack-of-t (p-value < 0.001), hinting at unaccounted-for factors or potential experimental errors. This highlights the need for further optimization and exploration of additional variables to rene the model's accuracy and predictive power.…”
Section: Evaluation Of the Bbd Modelmentioning
confidence: 93%
“…Only when accompanied by a similarly high adjusted-R 2 and an insignicant lack-of-t can truly infer a robust regression model. 66 Regarding the tested variables, two (X 3 , and X 4 ) of the four investigated factors exhibit statistically signicant individual effects on Ag@SeO 2 bmNP production. Notably, turmeric concentration has the most signicant impact, with the highest F value and a low p-value of less than 0.001, highlighting its crucial role in the biosynthesis process.…”
Section: Evaluation Of the Bbd Modelmentioning
confidence: 98%
“…Altowayti et al, 2020 reported the potential of mixed dried biomass of three bacterial strains Bacillus thuringiensis strain WS3, Pseudomonas stutzeri strain WS9 and Micrococcus yunnanensis strain WS11 in the removal of As (V) and As(III) and optimization of process parameters using ANN model. Artificial neural networks (ANN) were conducted by Elsayed et al, 2022 for modelling the biosorption of Co(II) by Pseudomonas alcaliphilaNEWG-2.…”
Section: Environmental Monitoring Based On Artificial Neural Network ...mentioning
confidence: 99%